Pengaruh Penggunaan Media Smart Board Alfabet Terhadap Kemampuan Keaksaraan Anak Usia Dini 5-6 Tahun Di Paud Sps Dahlia Serang Baru - Hartati, Dini; Darmiyanti, Astuti; Riana, Nancy (Peneliti.net, 2025)
The aim of this research is to find out how the literacy skills of early childhood 5-6 years old differ before and after being given treatment with the alphabet smart board media. The research method used is an experimental quantitative research method with a One Group Pretest – Posttest design. The population in this study was group B at PAUD SPS Dahlia Serang Baru. Sampling in this research used random sampling techniques. The sample in this study consisted of 14 children who were taken by random sampling. The data collection technique used in this research was an initial test (pretest), then implementation of the treatment (treatment), which in this study was carried out 8 times, and a final test (posttest). The data analysis techniques used are descriptive statistical analysis, Shapiro-Wilk normality test, homogeneity test and hypothesis testing, namely using the paired sample t test. Based on the results of this research, it can be concluded that children's literacy abilities before and after being given treatment using the alphabet smart board media have significant changes in the literacy abilities of early childhood 5-6 years. This is proven by the results of the paired sample t test, namely Sig. (2-tailed) 0.001 < 0.05, then the rule decided is that Ho is rejected and Ha is accepted, which means that the use of alphabet smart board media has a significant influence on the literacy abilities of early childhood children 5-6 years old at PAUD SPS Dahlia Serang Baru.